Integrated Architecture and Application Assumption of Earth-Space Communication and Remote Sensing Combination - Wenbo SU; Chi ZHANG; Niwei WANG; Zhichao QIN (天地一体化信息网络)
Remote sensing systems are important means of space-based Earth observation, due to issues such as delayed measurement and control commands, data transmission, data processing, and product distribution in the ＆quot;collection-processing-distribution＆quot; process, it is difficult to effectively achieve real-time intelligent remote sensing application services that cover all day, all weather, and the world.The combination of low earth orbit communication and remote sensing satellite constellations is an effective way to solve service delay and separate control problems in existing systems.It summarized the current situation of communication and remote sensing integration over the world, and then imagined the architecture, development stages, and service modes of the integration of communication and remote sensing.Finally, key technologies under the communication and remote sensing integration architecture were proposed, and the application process of communication and remote sensing integration used typical application scenarios were explored.